Wet-impregnated bimetallic Pd-Ni catalysts with enhanced activity for dehydrogenation of perhydro-N-propylcarbazole. (13th November 2020) - Chen, Xuedi; Li, Gen; Gao, Min; Dong, Yuan; Yang, Ming; Cheng, Hansong
Abstract: Palladium/platinum-based catalysts are widely used in the dehydrogenation process of Liquid Organic Hydrogen Carriers (LOHCs). The cost of noble metal has become a main drawback for LOHCs large-scale application. Partial replacement of Pd/Pt by other transition metals can be an effective solution. In this paper, we synthesize the bimetallic Pd–Ni catalyst by incipient wet impregnation and the catalytic dehydrogenation performance of perhydro-N-propylcarbazole (12H-NPCZ) as a LOHC candidate. Ni and Pd were impregnated on mesoporous alumina to obtain both monometallic and bimetallic catalysts, i.e. Pd/Al2 O3, Ni/Al2 O3 and Pd–Ni/Al2 O3 (Pd:Ni = 1:1) with total metal loading of 5 wt%, respectively. The above catalysts were characterized by N2 -adsorption/desorption, H2 -temperature programmed reduction, X-Ray diffraction, X-Ray photoelectron spectroscopy, Inductively coupled plasma - optical emission spectrometer, CO pulse adsorption and Transmission electron microscopy. The catalytic dehydrogenation results indicated that the bimetallic Pd–Ni/Al2 O3 showed best catalytic activity, followed by Pd/Al2 O3, commercial Pd/Al2 O3 and Ni/Al2 O3 . Notably, the catalytic activity of bimetallic was well maintained after 5 cycles at 200 °C with no degradation, indicating this bimetallic catalyst has potential prospect for large-scale application. Graphical abstract: Image 1 Highlights: Pd–Ni/Al2 O3 was prepared by incipient impregnation method. The catalytic activities were compared by dehydrogenation of perhydro-N-propylcarbazole. The bimetallic Pd–Ni/Al2 O3 showed best catalytic activity. The catalytic activity was well maintained after 5 cycles at 200 °C with no degradation.